The development process of bringing junior talents to the world-class stage in cross-country skiing - Sandbakk, Ø. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
In this keynote, I will discuss key elements of a comprehensive athlete development system in cross-country skiing, drawing on both research and practical experience.